Correlates of Maize Land and Livelihood Change Among Maize Farming Households in Mexico. (June 2015) - Eakin, Hallie; Appendini, Kirsten; Sweeney, Stuart; Perales, Hugo
Summary: We use classification tree analysis to identify the primary predictors of a suite of maize land use and livelihood outcomes for smallholder farmers in three regions of Mexico (Sinaloa, Mexico state, and Chiapas). Our analysis identifies regionally specific correlates with change in maize area, yield, and income, spanning demographic, environmental, and social development factors. Our results indicate that there may be opportunities for surplus production and market participation in some rain fed areas. We confirm the significance of regional and inter-regional heterogeneity in farmers' responses and strategies, underscoring the value of regionally specific policy interventions.